ANALISIS MANFAAT DAN BIAYA PROGRAM PRODUKSI BERSIH PADA INDUSTRI TEKSTII, - Lilies Setiartiti (FE UMY, 2015)
The rapid indu,strial and economrc growth experienced blt Indone:;iLt ,rory yuiii igo, has been accompanied by u senous deterioration ctf lhe counlrv's natural resource,s and enviromentol quality. IJ su,stuinnhle development i,\ b hc uchitvetl, St,xiuttion pro_ cesse:, producl, and seryices hayc lo he reorienled lo)4)(rds new pqll.rn, in order to both alleviate environmental .srress und hring better indu\trial productitiry This requires the development and use of new /)\rc) Ltnd manogenxent lools in industry Theoneofthisis Clectner Productiotts Systent (lleuner prochrctlotl is thc (ontinou,\ applicatio,n of an inlegrated preyentiye environmentul ,strdtegl, tp py6ggsses dn(l pro(luc.t !o reduce risks to humans and the environment. The researchJbcus on the textilc i,du:tries, which lhe production cqpacity about I ton per day, and e;f.fluent debits ahout 163,5 to 200 m3. Cleancr prodtrction systcm use the Non-oxidizing Microbiocide Sy:;tant, thqt will subtitutes applicution 0fbiocide whith ultraviolet light or ozon n coolittg svstem and waste ninimized processes. The purpbse of lhi.s rcsearch uas to compar( tht iu1n11 toward Lnrironnk,nt batw,,en cleaner prodtrlion and lhe older system. Thc other purposes y)as to exaninecl the cost sor)ing by using cl e one r produc I ion :y,s I e nt Economically, by using Bcnelit oncl ('ost An y.sis, rhe rcsrll of rhe research inLdictttect tlzat cleaner production systan i.s lLct:;ible.for indushies, bccetirsi of ; u) valuc oJ bcnefir and cost ratio more than l, h) Nct Present Vatue Rp.l I 603.2A2,$, c) internal rate ctf return 27,78o,4t. d)Pay Back Pcriocl 3 yeors and 3,5 tnonths. T'he other hands. Non-oxidiz_ mg Microbtocide qppointed th.tt t.hcre was tltfibrently about effluent characterisric be- Iween cleaner production antl thc r dar systenl, in parameter pH, BOD, COD, Suspenclert solid, and Secondary waste